Effects of Baduanjin Exercise on Rehabilitation of Patients With Mild to Moderate Parkinson’s Disease - Dong, Shuangshuang; Wang, Yiqing; Wei, Hongyu; Du, Shouyun; Li, Xiaojing; Zhu, Jianbing; Wang, Yi; Cai, Zenglin (Frontiers in Neuroscience, 2022)
Objectives Rehabilitation, aerobic exercise, and many traditional Chinese exercises are known to significantly improve balance in patients with Parkinson’s disease. Baduanjin, a traditional physical and mental exercise, has long been practiced for health care as it regulates organs, the nervous and motor systems. Methods We recruited 31 eligible participants. Patients underwent a 3-week Baduanjin program, including 35-min exercise daily. Scores on the Modified Unified Parkinson’s Disease Rating Scale (MDS-UPDRS), Non-motor Symptoms Scale (NMSS), and gait and balance tests were compared before and after the Baduanjin program. Results MDS-UPDRS-total (t = 4.669, P ≤ 0.001), MDS-UPDRS part-I (t = 5.805, P ≤ 0.001), MDS-UPDRS part-II (t = 5.234, P ≤ 0.001), MDS-UPDRS part-III (t = 3.274, P = 0.003), and NMSS (t = 4.815, P ≤ 0.001) scores significantly decreased after the 3-week intervention. Gait parameters like step (t = 2.289, P = 0.030) and cycle (t = 2.181, P = 0.038) durations also significantly improved, while Balance-check® indicators, including the total score (t = −2.147, P = 0.041) and grade (t = 3.432, P = 0.002) significantly differed before and after exercise. Conclusion Baduanjin exercise shows beneficial effects for non-motor symptoms, balance, gait, and daily activities in patients with Parkinson’s disease. Baduanjin can be included in the patients’ family exercise, which is conducive to their rehabilitation, as well as for obtaining important social and economic benefits. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [ChiCTR-IPR-17011875].